2000
DOI: 10.1292/jvms.62.1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Embryotropic Roles of Tissue Inhibitor of Metalloproteinase-1 in Development of "HanWoo"(Bos taurus coreanae) Oocytes Co-cultured with Bovine Oviduct Epithelial Cells.

Abstract: ABSTRACT. This study was conducted to purify a tissue inhibitor of metalloproteinase (TIMP)-1 in a serum-free medium conditioned with bovine oviduct epithelial cells (BOEC) and to evaluate its effect on development of "HanWoo" (Bos taurus coreanae) embryos to the blastocyst stage. In the first study using SDS-PAGE electrophoresis, the presence of 32 kDa proteins, which contains TIMP-1, was detected in the medium conditioned with BOEC, and TIMP-1 was then purified from the medium by gel filtration and HPLC tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The oviduct synthesizes and secretes many proteins in many species including rabbit (García et al, 2010), swine (Buhi and Alvarez, 2003), sheep and cattle (Nancarrow and Hill, 1995) which influence the gene expression of the developing embryos. Several proteins play an important role in embryo development and embryogenesis regulation (Insulin-like growth factor 1, Herrler et al, 1998;oviductin, Buhi and Alvarez, 2003; TIMP metallopeptidase inhibitor 1, Hwang et al, 2000;uteroglobin, Riffo et al, 2007;leptin, Zerani et al, 2005). The asynchrony associated with the advanced uterine environment could cause the death of less developed embryos (Wilde et al, 1988;Xie et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The oviduct synthesizes and secretes many proteins in many species including rabbit (García et al, 2010), swine (Buhi and Alvarez, 2003), sheep and cattle (Nancarrow and Hill, 1995) which influence the gene expression of the developing embryos. Several proteins play an important role in embryo development and embryogenesis regulation (Insulin-like growth factor 1, Herrler et al, 1998;oviductin, Buhi and Alvarez, 2003; TIMP metallopeptidase inhibitor 1, Hwang et al, 2000;uteroglobin, Riffo et al, 2007;leptin, Zerani et al, 2005). The asynchrony associated with the advanced uterine environment could cause the death of less developed embryos (Wilde et al, 1988;Xie et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in early embryo development seem to be associated with greater ES in the AA genotype than in the GG and AG genotypes at this stage of gestation, representing 32 and 25% of the SD for EES, and 80 and 65% of the SD for % CM, respectively. A disruption of the TIMP1 gene product is associated with a significant increase in uterine matrix metalloproteinase activity, leading to a negative effect on the development of embryos (Hwang et al, 2000;Nothnick, 2000Nothnick, , 2001a. Estellé et al (2006) reported greater expression of the TIMP1 gene in the oviduct at 62 h of gestation in the High line.…”
Section: Discussionmentioning
confidence: 99%
“…Some proteins have an important role in embryo development. Secretoglobin family 1A member 1 (SCGB1A1, also known as uteroglobin; Riffo et al, 2007), IGF1 (Lin et al, 2003), and tissue inhibitor of metalloproteinases 1 (TIMP1; Hwang et al, 2000) are involved in regulating the embryogenesis, angiogenesis, morphogenesis, and endometrial tissue remodeling processes that take place during gestation. Therefore, SCGB1A1, IGF1, and TIMP1 could explain part of the embryonic losses before implantation in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…They inhabit only the Korean peninsula, and are important for food industries in the Republic of Korea. Therefore, it is important to understand their physiology, metabolism and nutrition (Hwang et al , 2000). A recent study on the rumen microbiota of HanWoo steers using pyrosequencing of 16S rRNA genes reported that nearly all archaeal sequences form a new phlyogenetic lineage and are distinct from the known methanogens.…”
mentioning
confidence: 99%